Flexural and Shear Strengthening of High-Strength Concrete Beams Using near Surface Basalt Fiber Bars - Ahmed Ashteyat; Ala’ Taleb Obaidat; Ahmad Al-Khreisat; Mu’tasime Abdel-Jaber (Infrastructures)
Strengthening of reinforced concrete (RC) structures has become a primary challenge in civil engineering. Different materials and procedures have been used in order to repair or strengthen RC structures. In this research, the NSM-Basalt Bar (NSM-BFRP) technique was used to strengthen high-strength reinforced concrete beams in flexure and shear. Twelve beams were designed, constructed, and tested under four-point loads. Six of them were designed to have insufficient longitudinal steel reinforcement to make sure that the failure would be a flexural failure in the control beam. Whereas, the other six specimens were designed to have insufficient transverse steel reinforcement to make sure that the failure will be a shear failure in the control beam. All RC beams were strengthened using NSM-BFRP with different configurations except control specimens. The load deflection curve, the cracking pattern and the failure mode were evaluated. The experimental results reveal that NSM-BFRP bars significantly enhance the ultimate load capacity of high-strength concrete beams, with flexural capacity improvements of up to 33.33% and shear capacity enhancements of up to 63.5%. However, the use of BFRP bars also led to a shift in failure modes from flexural to shear, particularly in specimens with increased flexural reinforcement. The findings suggest that while NSM-BFRP bars are highly effective in strengthening concrete beams, careful consideration of the reinforcement configuration is necessary to avoid premature shear failure and ensure balanced structural performance.